Has the frequency of dental trauma and mouthguard use in elite handball players changed since 2005? - Guven, M.; Demirekin, Z. B.; Eroglu, E.; Akça, H. S. (International Journal of Research - GRANTHAALAYAH, 2023)
Background: The study on the incidence of dental trauma and the use of mouthguards in 2005 revealed that handball players in Turkey do not use mouthguards. This current study evaluates the changes up to 2021 and evaluates today's athletes' attitudes toward using mouthguards. Methods: The data were collected from 68 professional handball players through a questionnaire. The same questions of the 2005 study were asked concerning the incidence of dental trauma and mouthguard use. In addition, today's handball players' attitudes toward using mouthguards were also investigated. The data were analyzed with Minitab 17. Independent samples t-tests were used to compare quantitative data. Fisher's exact test was used for ratio comparisons (percentage), and the Pearson Chi-Square test was used to distribute categorical data. The statistical significance level was taken as p<0.050. Results: This study shows that the athletes have experienced minor dental trauma since 2005. However, the difference is not statistically significant (p=0.291). Moreover, there was no statistically significant difference between the distribution of dental injury types in the avulsion, crown fracture, and dislocation between 2005 and 2021 (p=0.431). While 77.4% of the athletes were aware of mouthguards in 2005, this rate has increased to 100% in 2021 (p<0.001). No mouthguard use was reported in the 2005 study, while 29% of the participants in 2021 reported mouthguard usage (p<0.001). The main reason for not wearing a mouthguard for the 2005 participants was lack of information, while in 2021, it was fear of speaking or breathing difficulties (p<0.001) Conclusions: Dental trauma remains a severe problem for handball players. It is pleasing that professional handball players in Turkey have started to use mouthguards. Dentists and sports managers should work together to reduce the frequency of dental trauma and prevent possible adverse effects.